Oriented collagen tubes combined with basic fibroblast growth factor promote peripheral nerve regeneration in a 15 mm sciatic nerve defect rat model. Issue 1 (21st August 2016) - Fujimaki, Hisako; Uchida, Kentaro; Inoue, Gen; Miyagi, Masayuki; Nemoto, Noriko; Saku, Taro; Isobe, Yoshihiro; Inage, Kazuhide; Matsushita, Osamu; Yagishita, Saburo; Sato, Jun; Takano, Shotaro; et al.
Abstract: We developed a new scaffold material—oriented collagen tubes (OCT)—and evaluated the potential of OCTs combined with basic fibroblast growth factor (bFGF) to repair of a 15 mm sciatic nerve defect in rats. The treatment groups consisted of OCT with adsorbed bFGF (OCT/bFGF group), OCT in phosphate‐buffered saline (PBS) (OCT/PBS group), and a no‐treatment group (Defect group). Functional evaluation of nerve regeneration was performed using the CatWalk system, and histological analyses of the defect sites were also performed. In rats treated with either OCT/bFGF or OCT/PBS, the walking function parameter of max contact area returned to normal levels by 4 weeks after grafting, and the regeneration of myelinated fibers was detected after 8 weeks. However, more regenerated myelinated fibers were observed in the OCT/bFGF group compared with the OCT/PBS group at 4 weeks. In addition, the max contact area and swing speed in the OCT/bFGF group were significantly recovered compared to the OCT/PBS and Defect groups at 8 weeks. Although the combination of bFGF and OCT was superior to OCT alone for nerve regeneration and functional recovery, the present findings demonstrate that OCT alone or in combination with bFGF accelerates nerve repair in a large peripheral nerve defect in rats. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 8–14, 2017.